Effects of Sb on structure, micro structure and electrical characteristics of Sb-modified (K0.41Na0.59)NbO3 ceramics - Le, Tran Uyen Tu (Hue University Journal of Science: Natural Science, 2023)
Lead-free (Na0.59K0.41)(Nb1-xSbx)O3 ceramic (x = 0 ÷ 0.12) were prepared by the solid phase reaction method. The influence of Sb concentration on the structure, microstructure and electrical properties of the ceramic was studied. Results indicate that the presence of pure perovskite phase was revealed by XRD patterns recorded for the ceramics, which also showed a shift in structure from orthorhombic to mixed rhombohedral and tetragonal with an increase in x value. At x = 0.06, the ceramics express the best microstructure, the particles were tightly packed with an average particle size of 1.76 µm. The (Na0,59K0,41)(Nb0,94Sb0,06)O3 ceramics have the best dielectric and ferroelectric properties: the ceramic density (r) is 4.48 g/cm3 (relative density: 98.7% of the theoretical value); highest dielectric constant at TC (emax) of 12031; dielectric constant at RT (ε) of 945; low dielectric loss (tanδ) of 0.15; and high remanent polarization (Pr) of 11,2 mC/cm2; and the reactance field (Ec) of 8.7 kV/cm, and the phase transition temperatures (TC) of 372 °C, and (TO-T) of 157 °C.